Using the Mind Mapping Technique for Better Teaching of Writing in English - Fitria Fitria (English Education Journal, 2016)
The aims of this study were to find out whether there would be any significant improvement in the ability of students taught to write in English using the Mind Mapping Technique (MMT) by comparison with students taught using another technique. It is further to investigate the effect of teaching writing to the first grade students at a high school in Banda Aceh, Indonesia, using MMT. This research was an experimental study, two classes were taken as the sample, a control group (CG) and an experimental group (EG), each with 32 students. The quantitative data was obtained from the results from the pre-tests and the post-tests of writing done by the students. The result of the quantitative data analysis can be seen from the result from the post-tests for each group where the mean of the post-test scores from the EG was 81, while that from the CG was 70. By comparing the t-test score and t-table score, the result of the t-test was 6.38, while the result of the t-table at a level of significance with α=0.05 was 1.68. Thus, the t-test score was higher than the t-table score. Hence, it can be concluded that the students who were taught using the MMT performed better at writing tasks than those who were taught by another technique. The analysis of the writing done by the students to investigate the effects of the MMT also showed that the students in the EG improved in every aspect (content, vocabulary, grammar, organization and mechanics) of writing since they were taught using MMT. After being taught using the MMT they could develop their ideas into good paragraphs and compose a well-written piece of writing.